2014
DOI: 10.1111/ger.12137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of root canal treatment and periapical radiolucency in elders: a systematic review

Abstract: In comparison to general adult populations, elders had: a much higher prevalence of NSRCT, a higher prevalence of PARL, a lower prevalence of PARL in NSRCT teeth, and a higher prevalence of PARL in untreated teeth. Teeth saved through NSRCT were preferentially retained by elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
(96 reference statements)
1
34
0
1
Order By: Relevance
“…The proportion of the world's population over 60 years of age is estimated to double from 12% to 22% between 2015 and 2050 according to World Health Organization data. A recent systematic review concluded that older people had higher endodontic needs and more untreated apical disease than other adults . Considering the current data, there will likely be a growing demand for geriatric endodontics as the number of natural teeth remaining in the jaws of the elderly adults in particular will presumably be higher.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The proportion of the world's population over 60 years of age is estimated to double from 12% to 22% between 2015 and 2050 according to World Health Organization data. A recent systematic review concluded that older people had higher endodontic needs and more untreated apical disease than other adults . Considering the current data, there will likely be a growing demand for geriatric endodontics as the number of natural teeth remaining in the jaws of the elderly adults in particular will presumably be higher.…”
Section: Discussionsupporting
confidence: 88%
“…A recent systematic review concluded that older people had higher endodontic needs and more untreated apical disease than other adults. 34 Considering the current data, there will likely be a growing demand for geriatric endodontics as the number of natural teeth remaining in the jaws of the elderly adults in particular will presumably be higher. Nevertheless, evaluating the effect of ageing on the structural and mechanical properties of teeth might contribute to the improved selection of treatment protocols and thus to the success of dental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…These longitudinal data were not inconsistent with a recent systematic review of cross‐sectional outcomes which reported a lower prevalence of PARL in the NSRCT teeth of elders than that for other adults. Cross‐sectional data describe the disease status of a population, capturing a single snapshot in time, but cannot tell us whether cases are in progress to healing or to failure.…”
Section: Discussionmentioning
confidence: 51%
“…Individuals accumulate NSRCT throughout their lives. Epidemiological data indicates that elders have a much higher prevalence of NSRCT than other adults. This could happen because valued teeth may be preferentially retained through NSRCT, less valued teeth may be preferentially extracted or failures are removed by extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, great care must be taken to avoid traumatizing the gingiva during rubber dam clamp placement, etc. Increased age does not influence end odontic outcomes; however, increased calcification can increase the level of technical difficulty (Hamedy et al, 2014).…”
Section: Systemic Issues Causing Complicationsmentioning
confidence: 97%